Gestión de la innovación en pequeñas y medianas empresas de Barranquilla - Colombia (2016)
The evolution of global trends characterized by economic, social and political openness, driving innovation management as a dynamic hub for the competitiveness and sustainability of small and medium Colombian enterprises (SMEs). This article aims to describe the management of innovation in small and medium enterprises in the service sector in the city of Barranquilla. The focus was quantitative with a type descriptive, cross-sectional research, using as a technique for data collection, application of a structured questionnaire to one intentional and probabilistic sample of 80 companies in the services sector. The results show that 50% of SMEs Innovation is associated with the development of new products and services, there being a responsible person who manages and allocates tasks based on your criteria and market requirement. It was concluded that innovation management requires clearly defned processes and planned in relation to the inclusion of the same innovation in administrative practices, aspect that leads to a major upgrade and professionalize responsible managers, and staff that composes.